Universal liquid-phase laser fabrication of various nano-metals encapsulated by ultrathin carbon shells for deep-UV plasmonics. Issue 25 (15th June 2017) - Yu, Miao; Yang, Chao; Li, Xiao-Ming; Lei, Tian-Yu; Sun, Hao-Xuan; Dai, Li-Ping; Gu, Yu; Ning, Xue; Zhou, Ting; Wang, Chao; Zeng, Hai-Bo; Xiong, Jie
Abstract : The exploration of LSPR beyond the usual visible waveband, for example within the UV or deep-UV regions, is of great significance due to its unique applications in secret communications and optics. Abstract : The exploration of localized surface plasmon resonance (LSPR) beyond the usual visible waveband, for example within the ultraviolet (UV) or deep-ultraviolet (D-UV) regions, is of great significance due to its unique applications in secret communications and optics. However, it is still challenging to universally synthesize the corresponding metal nanostructures due to their high activity. Herein, we report a universal, eco-friendly, facile and rapid synthesis of various nano-metals encapsulated by ultrathin carbon shells, significantly with a remarkable deep-UV LSPR characteristic, via a liquid-phase laser fabrication method. Firstly, a new generation of the laser ablation in liquid (LAL) method has been developed with an emphasis on the elaborate selection of solvents to generate ultrathin carbon shells, and hence to stabilize the formed metal nanocrystals. As a result, a series of metal@carbon nanoparticles (NPs), including Cr@C, Ti@C, Fe@C, V@C, Al@C, Sn@C, Mn@C and Pd@C, can be fabricated by this modified LAL method. Interestingly, these NPs exhibit LSPR peaks in the range of 200–330 nm, which are very rare for localized surface plasmon resonance. Consequently, the UV plasmonic effects of these metal@carbon NPs were demonstrated both by the observed enhancement in UV photoluminescence (PL) from the carbon nanoshells and by the improvement of the photo-responsivity of UV GaN photodetectors. This work could provide a universal method for carbon shelled metal NPs and expand plasmonics into the D-UV waveband.